The Development of an E-Module Based on Discovery Learning on Coordination System Material to Improve 4C Skills of High School Students - Pragiwati Setiana; Endah Peniati (Journal of Biology Education, 2023)
The results of interviews with biology teachers in class XI MIPA at SMA Negeri 1 Slawi show that the 4C skills of students in class XI MIPA are low due to the absence of a variety of teaching materials and that the role of the teacher as a teacher has not been implemented properly. Therefore, a discovery-learning-based e-module was developed on coordination material to improve students' 4C skills. The purpose of this study was to analyse the feasibility, readability, and practicality of using e-modules and the improvement of students' 4C skills on coordination system material. This type of research is research and development, and the research design used is the development research design, according to Thiagarajan et al. (1974). The instruments used in this study were the product validation questionnaire, teacher response questionnaire, readability questionnaire, student response questionnaire, pre-test and post-test questions, observation sheet, and peer assessment. The results of the study showed that the e-module was feasible to use, obtaining an average score of 92.97%. Students' readability of the e-module obtained a score of 96.48% with very good criteria. Students' responses to the practicality of using e-modules amounted to 89.82%, with very practical criteria. The discovery learning-based e-module developed on coordination system material has an effect on students in the form of increasing their 4C skills. The conclusion of this research is that e-modules based on discovery learning on coordination system material are feasible and practical to use in learning coordination systems, have very good readability, and are effective in improving the 4C skills of SMA Negeri 1 Slawi students.